Identification of resistant sources against collar rot disease in groundnut (Arachis hypogaea) incited by Aspergillus niger - GARIMA; YADAV, N K; MALIK, V K; DAHINWAL, ASHOK KUMAR; KUMARI, DEEPAK; SARAN, MAHENDRA; SHEORAN, NIHARIKA (The Indian Journal of Agricultural Sciences, 2024)
Collar rot disease incited by Aspergillus niger van Tiegham is one of the major constraint to groundnut (Arachis hypogaea L.) production in India. This fungus is ubiquitous, soil inhabitant causing severe reduction in seed germination. Infected seeds appear surrounded by black conidia and post-emergence infection occurs on collar region of plants leading to mortality of emerged seedlings at the seedling stage. Therefore, present study was carried out during rainy (kharif) seasons of 2022 and 2023 at Regional Research Station (CCS Haryana Agricultural University, Hisar, Haryana), Bawal, Haryana to identify the strategy of disease management by identification of new resistant lines which will be useful to develop introgression lines using marker-assisted backcrossing approach to improve disease resistance against soil-borne pathogens in popular groundnut varieties. A total of 245 groundnut genotypes were screened under natural epiphytotic field conditions in randomized block design (RBD) with three replications for their resistance against collar rot disease The results of the investigation indicated that 65 genotypes displayed resistant reactions among which ICGV-6285, GC-131-1, ICGV-06319, ICGV-02038, GC-100, GC-98, ICGV-02038, ICGV-7403, ICGV-7214, TG-37A and GC-133 exhibited the lowest collar rot incidence while, rest of the genotypes displayed moderately resistant, susceptible and highly susceptible reaction. Thus, these resistant genotypes could be utilized in the hybridization programme to develop high yielding groundnut variety with inbuilt resistance against collar rot of groundnut.